2016
DOI: 10.1007/978-3-662-49890-3_23
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Message Length in PMAC’s Security Bounds

Abstract: Abstract. Many MAC (Message Authentication Code) algorithms have security bounds which degrade linearly with the message length. Often there are attacks that confirm the linear dependence on the message length, yet PMAC has remained without attacks. Our results show that PMAC's message length dependence in security bounds is non-trivial. We start by studying a generalization of PMAC in order to focus on PMAC's basic structure. By abstracting away details, we are able to show that there are two possibilities: e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
(23 reference statements)
0
20
0
Order By: Relevance
“…Recently, Luykx et al [LPSY16] showed that one can construct a pair of messages which will collide with probability roughly /2 n , leading to an attack with advantage /2 n for q = 2 messages. However, their attack does not generalize to q messages.…”
Section: Security Of Pmac In the Random Permutation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Luykx et al [LPSY16] showed that one can construct a pair of messages which will collide with probability roughly /2 n , leading to an attack with advantage /2 n for q = 2 messages. However, their attack does not generalize to q messages.…”
Section: Security Of Pmac In the Random Permutation Modelmentioning
confidence: 99%
“…, γ to contain a large coset of a subgroup of GF (2 n ), and it's not clear if the sequence from [Rog04] contains such a set. Let us mention that for similar reasons the attack from [LPSY16] does not apply to the [Rog04] construction either.…”
Section: Variants Of the Pmac Constructionmentioning
confidence: 99%
“…[16][17][18] All the objects are defined as "Thing" such as smart-phones, smart-cars, industrial sensors, actuators, household appliances, and grid-networking under the platform of data and network communications. [10][11][12][13][19][20][21] Interestingly, the major works are focused to build network and topology for the concept of IoT. 12,13,[19][20][21] The IoT is already starting to kick-out to the applications of real-world: From home to office via car, smart-phone, health-card, national-card, and bank-card.…”
Section: Figure 1 Concept Of Authentication Encryptionmentioning
confidence: 99%
“…12,13,[19][20][21] The IoT is already starting to kick-out to the applications of real-world: From home to office via car, smart-phone, health-card, national-card, and bank-card. [10][11][12][13][19][20][21] Interestingly, the major works are focused to build network and topology for the concept of IoT. Therefore, a blackhole is developing for the emerging concept of the IoT, where the blackhole means lack of security, lack of trust, lack of integrity, lack of privacy under the communication channels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation